A practical approach to implementation of ecosystem‐based management: a case study using the Gulf of Maine marine ecosystem. Issue 3 (16th February 2010) - Altman, Irit; Blakeslee, April MH; Osio, Giacomo C; Rillahan, Christopher B; Teck, Sarah J; Meyer, John J; Byers, James E; Rosenberg, Andrew A
Abstract : The application of ecosystem‐based management (EBM) in marine environments has been widely supported by scientists, managers, and policy makers, yet implementation of this approach is difficult for various scientific, political, and social reasons. A key, but often overlooked, challenge is how to account for multiple and varied human activities and ecosystem services and incorporate ecosystem‐level thinking into EBM planning. We developed methods to systematically identify the natural and human components of a specific ecosystem and to qualitatively evaluate the strength of their interactions. Using the Gulf of Maine marine ecosystem as a case study, we show how these methods may be applied, in order to identify and prioritize the most important components to be included in an EBM plan – particularly the human activities that are the strongest drivers of ecosystem change and the ecosystem services most threatened by cumulative and indirect effects of these activities.